Comparison of the effectiveness of play therapy with and without attachment-based parent training on reducing aggressive behavior in children with oppositional defiant disorder - Akbari, Akram; Monirpour, Nader; Mirzahoseini, Hsasan (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to evaluate the effectiveness of play therapy with and without attachment-based parental training on the level of aggression in children with oppositional defiant disorder. Methods: The method of this study was quasi-experimental with pre-test design and follow-up with a control group. The statistical population of the study was children aged 4 to 6 years in Tehran. A multi-stage random sampling method was used in this study. First, eleven districts were randomly selected from 22 districts of Tehran and then one kindergarten was selected from each district of 11 districts by using a convenience random method. After screening by Gadow and Sprafkin (1984) Children Symptoms Inventory and clinical interviews, 45 children were selected and randomly assigned to three experimental and control groups (15 children in each group). The Play Therapy Experimental Group 1 underwent the intervention of Barclays training package (2006) and the Play Therapy Experimental Group 2 underwent attachment-based parental training for eight 90-minute sessions, and the control group did not receive any training. All three groups were assessed in the pre-test, post-test and follow-up stages using the Achenbach (1990) Children Behavioral Disorders Checklist. The collected data were analyzed using repeated measures variance. Results: The results of this study showed that play therapy (F = 6.17, P = 0.021) and play therapy of attachment-based parental training (F = 5.89, P = 0.027) were effective in reducing aggression in children with oppositional defiant and this effect persisted during the follow-up phase. Post-hoc test also showed that attachment-based play therapy is more effective. Conclusion: The results showed that play therapy combined with attachment-based interventions is effective in reducing aggression in children with oppositional defiant disorder and these two methods can be used to reduce aggression in these children.